Editor's Choice – Interventions to Achieve Functionality in Newly Created Arteriovenous Fistulas in the Shunt Simulation Study Cohort. (April 2023) - van Vliet, Letty V.; Zonnebeld, Niek; Bouwman, Lee H.; Cuypers, Philippe W.; Huisman, Laurens C.; Lemson, Susan; Schlösser, Felix J.; de Smet, André A.; Toorop, Raechel J.; Snoeijs, Maarten G.; ,; Delhaas, Tammo; et al.
Abstract : Objective: Although observational cohort studies report that interventions to achieve functionality are clinically successful in 85% of patients, the proportion of newly created autologous arteriovenous fistulas that result in functional vascular access typically is only 70 – 80%. To address this discrepancy, the selection and outcomes of interventions to achieve functionality in a multicentre prospective cohort study were analysed. Methods: The Shunt Simulation Study enrolled 222 patients who needed a first arteriovenous fistula in nine dialysis units in The Netherlands from 2015 to 2018 and followed these patients until one year after access creation. In this observational study, the technical and clinical success rates of interventions to achieve functionality based on lesion and intervention characteristics were analysed and the clinical outcomes of arteriovenous fistulas with assisted and unassisted functionality were compared. Results: For patients who were on dialysis treatment at the end of the study, unassisted fistula functionality was 54% and overall fistula functionality was 78%. Thirty-four per cent of arteriovenous fistulas required an intervention to achieve functionality, 68% of which eventually became functional. Seventy-five per cent of these interventions were percutaneous balloon angioplasties of vascular access stenoses. Patients with clinically successful interventions to achieve functionality had larger pre-operative vein diameters (2.8 ± 1.0 mm vs. 2.3 ± 0.6 mm, p = .036) and less often presented with thrombosed fistulas than patients with unsuccessful interventions (7% vs. 43%, p = .006). Arteriovenous fistulas with assisted functionality had similar secondary patency as fistulas with unassisted functionality (100% and 98% at six months, p = .44), although they required more interventions to maintain function (2.6 vs. 1.7 per year; rate ratio 1.52, 95% CI 1.04 – 2.18, p = .032). Conclusion: Interventions to achieve functionality were needed in about a third of newly created arteriovenous fistulas. Most thrombosed fistulas were abandoned, and when selected for thrombectomy rarely reached clinical success. On the other hand, interventions to achieve functionality of patent fistulas had high clinical success rates and therefore can be done repeatedly until the fistula has become functional.